Progressive Web Apps (PWA) for YII Framework Enrichment - Basri Basren (Journal of Telematics and Informatics, 2018)
Framework YII is a high-performance, component-based PHP framework for large-scale Web application development. YII provides maximum reusability in web programming and is able to increase development speed significantly. The YII framework provides many advantages ranging from programming architecture using MVC concepts, ORM database management features, Form validation, authorization and authentication, caching, and more. However, So far framework YII does not provide features that make the website is installable and can be accessed offline. To create a website that is installable and can be accessed offline, then the framework YII will be added service worker and manifest. Manifest is a simple JSON file that gives users the ability to save bookmark sites to the home screen. While the service worker is a script that runs the browser in the background, separate from the web page, and does not require a web page or user interaction to run it. Technically, Service Worker provides script network proxies in web browsers to manage web / HTTP requests programmatically. The Service Worker is able to efficiently cache mechanisms and enable websites to be accessed offline. This study aims to implement service worker and manifest in YII 2 Basic template framework in progressive web app development